Assessment of awake bruxism in undergraduate students, using Ecological Momentary Assessment, through WhatsApp - Souza Camargo, Elisa; de Rezende e Cota, Ana Flávia; Ramos Garanhani, Roberto; Kern Di Scala Andreis, Patricia; Ágatha Schneider, Neblyssa; Maia de Oliveira Borges Paraná, Camila; Schappo, Cláudia; Stuginski-Barbosa, Juliana; Mastriani Arantes, Ana Carolina; Ignácio, Sérgio Aparecido (Brazilian Journal of Implantology and Health Sciences, 2023)
This study assessed awake bruxism (AB) in undergraduate students using WhatsApp and examined the association of this behavior with quality of life and anxiety. The sample was composed of 36 healthy young adults of both genders, with an average age of 20.74 years. AB behaviors (teeth contact, teeth clenching, teeth grinding and mandible bracing) and relaxed jaw muscles were reported with Ecological Momentary Assessment, through WhatsApp, 15 times a day, for 7 days, between 8:00 am and 7:00 pm. Quality of Life (QoL) and anxiety were assessed using the SF-36 and GAD-7 questionnaires, respectively. The Mann-Whitney U non-parametric, Pearson and Spearman correlation and Pairwise non-parametric multiple comparisons 2- to-2 tests were used. The frequency of AB was 40.7%. The most frequent AB behavior was teeth contact (23.1%). Higher frequency of AB occurred on weekdays (42.3%) compared to the weekend (35.5%) (p<0.05). There was a negative correlation of AB behaviors and mandible bracing with the QoL - emotional aspects domain (p<0.05) and positive correlation of mandible bracing with anxiety (p<0.01). There was no difference between genders for QoL, anxiety and AB behaviors (p>0.05). This study highlights the importance of AB and anxiety control to improve undergraduate students’ quality of life.